2021
DOI: 10.1007/s12687-021-00538-z
|View full text |Cite
|
Sign up to set email alerts
|

Participation in genetic research among Latinx populations by Latin America birth-residency concordance: a global study

Abstract: Latinx populations are underrepresented in DNA-based research, and risk not benefiting from research if underrepresentation continues. Latinx populations are heterogenous; reflect complex social, migration, and colonial histories; and form strong global diasporas. We conducted a global study using a survey tool (Amazon's Mechanical Turk portal) to ascertain willingness to participate in genetic research by Latin America birth-residency concordance. Participants in the global study identified as Latinx (n=250) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Although the data we present addresses a recognized gap in genetic research in psychiatry (De Ver Dye et al, 2021), two limitations in our study must be considered. The lack of previous BD GWAS in LAT populations impedes us from having a LAT discovery GWAS to inform our PRS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the data we present addresses a recognized gap in genetic research in psychiatry (De Ver Dye et al, 2021), two limitations in our study must be considered. The lack of previous BD GWAS in LAT populations impedes us from having a LAT discovery GWAS to inform our PRS.…”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, genetic studies in psychiatry have primarily focused on EUR populations (Peterson et al, 2019), failing to address heterogeneity arising from population diversity (De Ver Dye et al, 2021; Martin et al, 2019). For BD, few GWAS have been performed outside of EUR ancestry, with the exception of an initial small study in an African American sample and a more recent larger study of BD and schizophrenia in a diverse cohort that included more than 1,000 African American participants with BD (Bigdeli et al, 2021; Smith et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid review reported concerns about the assumptions made regarding non-participation in genomic studies. Concerns included those related to privacy (Buseh et al, 2013; Abadie and Heaney, 2015 ; Simon et al, 2017 ; Garrison et al, 2019 ; Lee et al, 2019 ; Reddy et al, 2020 ; De Ver Dye et al, 2021 ; Hendricks-Sturrup and Johnson-Glover, 2021 ), stigmatisation (Marsh et al, 2013 ; Abadie and Heaney, 2015 ; Faure et al, 2019 ), commodification of data leading to dispossession (Abadie and Heaney, 2015 ) and re-use of data beyond the scope of the original research 9 (de Vries et al, 2014 ); for example, by commercialisation of the research and unjust corporate profiteering (Lee et al, 2019 ). It was noted that whilst such concerns may be common amongst other groups, they might be heightened for those from underserved groups due to experiences of stigmatisation, discrimination and prejudicial judgement (Abadie and Heaney, 2015 ), 10 particularly in cases of disease-related stigma (Ali-Khan and Daar, 2010 ; Faure et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that many ancestries are underrepresented in genomic databases and studies. Considering the heterogeneity of the LatAm population, the continent is especially sensitive to this (De Ver Dye et al, 2021;Borda et al, 2023). The gap is critical when preliminary analyses of the ClinGen criteria are applied, especially when an inherited but undescribed variant is detected in a candidate gene in databases as it is not possible to discard or consider it with confidence for further analyses (Step 5, Figure 3).…”
Section: Challengesmentioning
confidence: 99%